2005
DOI: 10.1038/sj.eye.6701730
|View full text |Cite
|
Sign up to set email alerts
|

Stargardt's disease and retinitis pigmentosa: different phenotypic presentations in the same family

Abstract: Figure 4 Fundus photograph of the 32-year-old brother.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Transmission of disease can vary from person to person, even within the same family. [45] Genetic research has identified nearly about 500 genes that contribute to inherited eye diseases. The inheritance pattern of Stargardts is mostly autosomal recessive although a small number may be autosomal dominant.…”
Section: Discussionmentioning
confidence: 99%
“…Transmission of disease can vary from person to person, even within the same family. [45] Genetic research has identified nearly about 500 genes that contribute to inherited eye diseases. The inheritance pattern of Stargardts is mostly autosomal recessive although a small number may be autosomal dominant.…”
Section: Discussionmentioning
confidence: 99%
“…These include Stargardt disease, fundus flavimaculatus, RP, and cone–rod dystrophy. The different phenotypes reflect the different tissues in which the ABCA4 gene is expressed, including the photoreceptors and the retinal pigment epithelium [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%